A Bibliometric Analysis of Mental Exhaustion Research among University Students: Mapping the Landscape - Yusoff, Yusliena; Tahar, Emiza; Aziz, Inayah Abdul; Jusoh, Rohayati; Nasir, Noor Emilina Mohd (Advances in Social Sciences Research Journal, 2024)
The prevalence of mental exhaustion among university students is an escalating problem that severely affects their academic performance and overall well-being. This study uses bibliometric analysis to map the research landscape on mental exhaustion among university students. Using the Scopus database for the period 2004-2023, this study examined publication trends, identified prominent authors and research clusters, assessed citation patterns and analysed co-occurring keywords. The Scopus database was selected due to its comprehensive coverage of scientific texts from different fields. The results show that the number of publications on mental exhaustion among university students has increased significantly over the past two decades. This increase reflects the growing recognition of the impact of this issue on students’ well-being and academic success. In addition, the analysis has identified prominent clusters of research focusing on specific areas such as contributing factors, coping mechanisms and the effectiveness of interventions to reduce psychological exhaustion. This bibliometric analysis provides a comprehensive overview of the research landscape on mental exhaustion in university students. The findings provide valuable perspectives for researchers, educators and policy makers seeking to understand and address this important issue. The study highlights the growing interest that will enable future research to develop effective techniques to promote mental wellbeing.